2021
DOI: 10.1002/joc.7031
|View full text |Cite
|
Sign up to set email alerts
|

Importance of regional indices of atmospheric circulation for periods of warming and cooling in Svalbard during 1920–2018

Abstract: The Arctic has experienced prominent climate warming, at the beginning of the 20th century and currently. Comparing the driving mechanism during these periods helps to explain the causes of contemporary climate change. Our study explores the impact of regional circulation on Svalbard's surface air temperature (SAT, 2 m above ground). We used air temperature data from Svalbard Airport, Bjørnøya stations, and three regional circulation indices that describe the frequency of cyclonic conditions, zonal circulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…AC plays a much greater role in shaping weather and climate in the Norwegian Arctic than elsewhere on the globe. Climate model studies have shown that changes in response to climate changes are strongest and quickest in the Arctic (e.g., Turner and Marshall 2011;Przybylak 2016;Łupikasza et al, 2021). A characteristic feature of AC over Spitsbergen is its increased cyclonic activity, conditioned by the island's location near the Arctic front (Niedźwiedź 2013a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AC plays a much greater role in shaping weather and climate in the Norwegian Arctic than elsewhere on the globe. Climate model studies have shown that changes in response to climate changes are strongest and quickest in the Arctic (e.g., Turner and Marshall 2011;Przybylak 2016;Łupikasza et al, 2021). A characteristic feature of AC over Spitsbergen is its increased cyclonic activity, conditioned by the island's location near the Arctic front (Niedźwiedź 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…AC also affects the extent of sea ice in the Arctic (Ding et al, 2017). In addition, changes happening in the Arctic are associated not only with positive feedback mechanisms-"Arctic amplification" (Serreze and Barry 2011)but also with changes in the extent of sea ice (Ding et al, 2017) and the reshaping of the pressure field and atmospheric circulation (Przybylak 2002;Łupikasza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the positive trend in autumn precipitation is one of the highest in Svalbard (Førland et al 2020). Nonetheless, the meteorological data from the PPS have rarely been analyzed in recent studies (e.g., Serreze et al 2015;Nordli et al 2020;Przybylak and Wyszyński 2020;Łupikasza et al 2021).…”
Section: Introductionmentioning
confidence: 99%